Proving triptycene homoconjugation with the same chromophore but different connectivity to the core: dedicated to Prof. Dr. Peter Bäuerle on the occasion of his 76th birthday - Elbert, Sven; Kirschbaum, Tobias; Rominger, Frank; Mastalerz, Michael (Organic materials, 2021)
Homoconjugation is a phenomenon discussed for various π-systems where classical conjugation is broken by e.g. methylene units but still a stabilization by electronic communication exists. In this respect, triptycene with its rigid C3 symmetric geometry is an ideal scaffold to study this phenomenon. Although several studies based on triptycene strengthen the hypothesis of homoconjugation, in all described cases the electronic communication through space relies on different π-blades. Here, two triptycenes are presented having the exact same π-extended chromophore, but differently annulated to the bicyclic core. Both compounds were investigated by spectroscopic as well as computational means and compared with the corresponding model compound, elucidating the influence of the attachment site to the triptycene core on potential homoconjugation.
Gesehen am 14.02.2022
Keywords: Festschrift